Implementation Of The Independent Policy Learning Independent Campus To Improve Competency Of Graduates Of Private Collections - Sukirno, Sukirno; Tutty Rokhayari Rosa, Ade; Iriantara, Yosal; Rosmaladewi, Okke (International Journal of Educational Research & Social Sciences, 2022)
The role of universities is needed in preparing superior human resources who are able to compete globally. Universities must adapt quickly in preparing students' new skills and competencies to face these new challenges. In order to prepare students for increasingly rapid social, cultural and technological developments, student competencies must be able to compete in this global era. Link and match not only with the world of industry and the world of work but also with a rapidly changing future. Implementation of mbkm using a strategic management approach, namely organizing, operational planning, allocation of resources with indicators of preparation and allocation of budgets, and management of human resources. Research methods with a qualitative approach and case study research methods. The research was conducted at stt mandala and itg. Methods of collecting data by interview, observation and documentation. The implementation of mbkm to improve has been carried out but not all mbkm activities or programs have been followed. Its implementation will continue to be improved so that all mbkm policies can be implemented optimally. Higher education commitments in implementing mbkm with an understanding of the urgency and relevance of mbkm, kpi and clustering.